Jaume Miravitlles and Marxism: a Twentieth-Century Voyage - Pujol, Enric (Journal of Catalan Intellectual History, 2012)
This article examines the political career of writer and journalist Jaume Miravitlles i Navarra (Figueres, 1906 – Barcelona, 1988). It proposes that the importance of his contributions to intellectual thought and politics deserve reassessment, partly because Miravitlles’s political progress was typical of certain left-wing European intellectuals during the period in discussion: of those whose initiation in politics was full-blooded Leninism, but who then progressively distanced themselves from Soviet ideology and finally became profoundly critical of political Marxism. Miravitlles played a leading role in the Spanish Civil War of 1936–1939, when he headed the Generalitat’s Propaganda Commissariat. After 1939, in exile, he became one of the leading narrators of human experience during this period of war and revolution, a role that he reaffirmed on his return to Catalonia in 1963. key words: Leninism, the avant-garde, Salvador Dalí, the Workers’ and Peasants’ Bloc (Bloc Obrer i Camperol), the Republican Left of Catalonia (Esquerra Republicana de Catalunya), the Civil War, the Propaganda Commissariat (Comissariat de Propaganda), exile, cold war, historiography, political thought.